Identifikasi Permasalahan Guru dalam Pelaksanaan Pembelajaran Matematika Materi Penjumlahan dan Pengurangan - Nina Suryani; I Ketut Widiada; Muhammad Makki (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The teacher has difficulty in understanding students about certain materials, in this case the teacher reveals that learning mathematics is one of the difficult subjects to teach to students. These problems can be seen from their ability to solve mathematical problems which are still low. This study aims to measure the difficulties faced by teachers in the implementation of mathematics learning in addition and subtraction for grade 2 at SDN Gugus V Cakranegara in the 2021/2022 academic year so that they can find out the highest problems faced by teachers based on the components of the implementation of learning. This research method is a descriptive method with a quantitative approach. Data collection techniques using interviews and questionnaire sheets. Analysis of the data using the percentage formula. The results showed that the intensity of the difficulties faced by teachers in the implementation of addition and subtraction mathematics learning at SDN Gugus V Cakranegara in the 2021/2022 academic year was included in the medium category as many as 9 teachers with a percentage of 90% and the highest problems faced by teachers in the implementation of learning mathematics materials. addition and subtraction, namely in conveying material and choosing the right media in learning mathematics with addition and subtraction material as many as 4 people with a percentage of 40%.